Epidemiology, Virulence and Antimicrobial Resistance of Escherichia coli Isolated from Small Brazilian Farms Producers of Raw Milk Fresh Cheese - Ribeiro, Laryssa Freitas; Rossi, Gabriel Augusto Marques; Sato, Rafael Akira [UNESP]; de Souza Pollo, Andressa [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Amaral, Luiz Augusto do [UNESP]; Fairbrother, John Morris (MDPI, 2024)
This study aimed to identify contamination sources in raw milk and cheese on small farms in Brazil by isolating Escherichia coli at various stages of milk production and cheese manufacturing. The study targeted EAEC, EIEC, ETEC, EPEC, STEC, and ExPEC pathotypes, characterizing isolates for the presence of virulence genes, phylogroups, antimicrobial susceptibility, and phylogenetic relationships using PFGE and MLST. The presence of antimicrobial resistance genes and serogroups was also determined. Three categories of E. coli were identified: pathogenic, commensal, and ceftriaxone-resistant (ESBL) strains. Pathogenic EPEC, STEC, and ExPEC isolates were detected in milk and cheese samples. Most isolates belonged to phylogroups A and B1 and were resistant to antimicrobials such as nalidixic acid, ampicillin, kanamycin, streptomycin, sulfisoxazole, and tetracycline. Genetic analysis revealed that E. coli with identical virulence genes were present at different stages within the same farm. The most frequently identified serogroup was O18, and MLST identified ST131 associated with pathogenic isolates. The study concluded that E. coli was present at multiple points in milk collection and cheese production, with significant phylogroups and high antimicrobial resistance. These findings highlight the public health risk posed by contamination in raw milk and fresh cheese, emphasizing the need to adopt hygienic practices to control these microorganisms.
Keywords: antimicrobial resistance; dairy; enterobacteria; food microbiology; foodborne pathogens